Facilitating the article of association and bylaws preparation of the As-Sakinah Cooperative, Regional Leaders of 'Aisyiyah Malang City - Fadilla Muhammad Mahdi; Rahayu Hartini; Tinuk Dwi Cahyani (Universitas Muhammadiyah Magelang, 2023)
The As-Sakinah Cooperative in Malang City is a cooperative that is in the process of converting to a sharia cooperative. However, this cooperative does not yet have a new draft of article of association and bylaws. Changes in the contents of the article of association and bylaws need to be made because there are some fundamental changes in the conversion to a sharia cooperative, such as changes to the organizational structure, name and operational activities. The service team tries to help solve the problem through workshops to discuss the contents of the new article of association and bylaws. This draft document, the article of association and bylaws, will be ratified through a meeting of cooperative members.